2016
DOI: 10.1007/s00436-016-5141-z
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the virulence determination mechanisms in a local Toxoplasma strain (T.gHB1) isolated from central China

Abstract: Several rhoptry proteins (ROPs) have been confirmed to be critical virulence factors of Toxoplasma gondii strains from North America and Europe. The two active kinases ROP17 and ROP18, and pseudokinase ROP5 were thought to be the key determinants of parasites' virulence in laboratory mice. Given the genetic diversity of Toxoplasma strains from different geographical regions, the virulence determinants in other strains, particularly the ones that are phylogenetically distant to the North American and European s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Phylogenetic analyses of T. gondii isolates based on introns which are selectively neutral loci are thought to provide an unbiased estimation, while secretory antigens, known to be functionally related to virulence and infectivity in the host (GRA6, GRA7 and ROP18) (Shwab et al, 2016;Zhang et al, 2016), are also considered capable of revealing great genetic diversity because they are frequently under selective pressure (Miller et al, 2004;Pena et al, 2008;Sundar et al, 2008). However, on the basis of these genes, phylogenetic analysis found that the avirulent TgCtwh6and virulent Chinese I (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Phylogenetic analyses of T. gondii isolates based on introns which are selectively neutral loci are thought to provide an unbiased estimation, while secretory antigens, known to be functionally related to virulence and infectivity in the host (GRA6, GRA7 and ROP18) (Shwab et al, 2016;Zhang et al, 2016), are also considered capable of revealing great genetic diversity because they are frequently under selective pressure (Miller et al, 2004;Pena et al, 2008;Sundar et al, 2008). However, on the basis of these genes, phylogenetic analysis found that the avirulent TgCtwh6and virulent Chinese I (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The infected cell cultures were monitored microscopically over 7 days after infection. Then, the cells were fixed with 4% paraformaldehyde and stained for 10 min with 2% crystal violet to visualize and count plaques formed by the growing parasites by using inverted microscope (Wang et al, 2016b; Zhang et al, 2016). …”
Section: Methodsmentioning
confidence: 99%
“…Also, this increased efficiently has made it possible to use non-laboratory adapted strains for genetic studies which were previously difficult to modify 13 . Even though in its infancy, CRISPR/Cas9 has already been used to make gene disruptions 2 13 17 18 48 49 , tag genes 17 , and make gene knockouts 16 19 50 51 52 53 54 in T. gondii , promising to be a useful tool for many other studies in the future.…”
Section: Discussionmentioning
confidence: 99%